On the origin of the seasonal and interannual T–S variability of the inflow through the Strait of Gibraltar - García-Lafuente, Jesús; Naranjo-Rosa, Cristina Belén; Sánchez-Leal, Ricardo; Sammartino, Simone; Bellanco, María Jesús; Sánchez-Garrido, José Carlos; Soto-Navarro, Francisco Javier (Elsevier, 2015)
Different datasets have been analyzed to identify the origin of the temperature and salinity seasonal and interannual fluctuations in the surface layer of the eastern North Atlantic Ocean, close to the Gulf of Cadiz. The analysis was motivated by the surprising short-term salinity trend recorded by a monitoring station deployed in the Atlantic layer of the Strait of Gibraltar between years 2003 and 2007, which has been described and investigated by Millot (2007. Geophys. Res. Lett. 34, L21609. doi:10.1029/2007GL031179.). Temperature and salinity display similar annual cycles whose maxima occur by the end of the year, the former leading the latter by one month approximately. Despite their similarities, their origin is not the same. More than 80% of the variability of the temperature seasonal cycle is accounted for by the annual cycle of surface heat flux, while advective fluxes are secondary. This is not true for salinity, which both seasonal and interannual fluctuations are shaped by the advection and the evaporative annual cycle jointly. For the advection contribution, the identified external agent is the wind stress that drives the upwelling season in the eastern mid-latitude boundary of the North Atlantic. Vertical advection of salinity associated with the Ekman pumping and horizontal advection caused by the upwelling jet and the fluctuations of the North Atlantic Subtropical Gyre are behind the local advective changes. The strengthening (weakening) of the seasonal upwelling in summer (winter) decreased (increased) the local salinity in the Gulf of Cadiz, giving rise to the observed cycle in the data recorded at Gibraltar. Short term trends in the wind-inducing upwelling off the Iberian Peninsula during the above mentioned period triggered concomitant changes of the salinity in the waters that fed the inflow and produced the short–term trend observed in the Strait of Gibraltar.
Se adjunta la versión postprint aceptada, que incluye las correcciones de de los revisores, debido a que la editorial tiene los derechos de copyright y no permite la difusión en acceso abierto de la versión publicada. Puede accederse a la misma a través del DOI que se incluye en los datos de la publicación.
Keywords: Mares y océanos - Temperatura - Proceso de datos - Gibraltar (Estrecho); Salinidad - Proceso de datos - Gibraltar (Estrecho); Gibraltar (Estrecho) - Clima - Observaciones - Proceso de datos; Gulf of Cádiz; North Atlantic subtropical gyre; Upwelling season; Surface and advective fluxes; Seasonal signal